“Repentance And Forgiveness”: The Place Of Political Fanaticism In Nigeria’s Democratic Woes - Ikem Godspower Ujene (Universitas Negeri Makassar, 2021)
The social qua social space known as Nigeria has been plagued by political maladministration, socio-economic misguide and behavioural nonchalance. In the light of the above, political office holders are more often than not fingered as both the cradle and the grave of this copious generational dilema. It is however unfortunate that the sheer inability to see this problem from a wholesome perspective- with emphasis on the electorate, has infused a fate-like sense of powerlessness in the general public. Although tons of theoretical and empirical studies exist on the issue at hand, there is a sense in which this particular study inputs the blame of Nigeria’s underdevelopment on the electorate- a shift from both academic and professional norma. The paper theorizes using Tajfel’s social identity that group identification has occasioned political fanaticism and this in turn engenders multifaceted underdevelopment. The paper further recommends as a way of conclusion, the need for a thorough consociational system of governance in the Nigeria’s political space. This will help in wholesomeness to alleviate the fear of domination by the majority ethnic groups among other solutions.